2020
DOI: 10.1186/s12864-020-6558-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study (GWAS) reveals genetic loci of lead (Pb) tolerance during seedling establishment in rapeseed (Brassica napus L.)

Abstract: Background: Lead (Pb) pollution in soil has become one of the major environmental threats to plant growth and human health. Safe utilization of Pb contaminated soil by phytoremediation require Pb-tolerant rapeseed (Brassica napus L.) accessions. However, breeding of new B. napus cultivars tolerance to Pb stress has been restricted by limited knowledge on molecular mechanisms involved in Pb tolerance. This work was carried out to identify genetic loci related to Pb tolerance during seedling establishment in rap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…A recent GWA study in wheat identified five loci ( qSCd−1A , qSCd−1D , qZn−2B1 , qZn−2B2 , and qFe−6D) associated with Cd stress tolerance ( Safdar et al, 2020a ). Analysis of a large collection of rapeseed accessions identified four QTLs and underlying candidate genes, including GSTUs, BCATs, UBP13, TBR , and HIPP01 , responsible for Pb tolerance ( Zhang et al, 2020a ). GWAS investigation on rice grains for Fe and Zn traces have identified novel marker-trait associations with a phenotypic variation of 2.1–53%, which could be helpful to identify candidate genes for improving Fe and Zn tolerance ( Bollinedi et al, 2020 ).…”
Section: Seven-(omics)-based Approaches To Improve Toxic Metals/metalloids Tolerance In Plantsmentioning
confidence: 99%
“…A recent GWA study in wheat identified five loci ( qSCd−1A , qSCd−1D , qZn−2B1 , qZn−2B2 , and qFe−6D) associated with Cd stress tolerance ( Safdar et al, 2020a ). Analysis of a large collection of rapeseed accessions identified four QTLs and underlying candidate genes, including GSTUs, BCATs, UBP13, TBR , and HIPP01 , responsible for Pb tolerance ( Zhang et al, 2020a ). GWAS investigation on rice grains for Fe and Zn traces have identified novel marker-trait associations with a phenotypic variation of 2.1–53%, which could be helpful to identify candidate genes for improving Fe and Zn tolerance ( Bollinedi et al, 2020 ).…”
Section: Seven-(omics)-based Approaches To Improve Toxic Metals/metalloids Tolerance In Plantsmentioning
confidence: 99%
“…One of them is the genome-wide association study (GWAs), used to connect plant phenotypes with candidate marker genes. This tool has lately been used to describe nine potential candidate genes related to the Pb-tolerance in Brassica napus (Zhang et al, 2020). Using the GWAs approach, we aim to improve the fragmentary picture of genes responsible for Pb tolerance taking advantage of the variability present in natural accessions of A. thaliana.…”
Section: Introductionmentioning
confidence: 99%